THE EFFECT OF PjBL-STEM MODEL ON COGNITIVE ABILITY OF STUDENTS IN PHASE D OF THE MATTER OF VIBRATION, WAVES AND LIGHT SUBJECT ON 8TH GRADE - Sari, Fine Dwina; Putri, Rahmah Evita; Oktavia, Rani; Putri, Azza Nuzullah (SEMESTA: Journal of Science Education and Teaching, 2025)
Cognitive ability is one of the essential aspects emphasized in the Merdeka Curriculum. One of the ways to enhance students’ cognitive ability is by applying the Project Based Learning-STEM (PjBL-STEM) model. This research was motivated by observations conducted on Grade VIII students at SMPN 21 Padang during the 2024/2025 academic year. The observations revealed that although the teacher implemented the PjBL-STEM model, its application was not fully optimal. The purpose of this study was to determine the effect of the PjBL-STEM learning model on students’ cognitive ability on the topic of vibration and wave. This study employed a quasi-experimental method with a posttest control group design. Purposive sampling was used to select the samples. Grade VIII students taught using the PjBL-STEM model served as the experimental group, while another Grade VIII class taught using conventional discovery learning served as the control group. The research instrument was an objective written test. The collected data were analyzed using normality, homogeneity, and hypothesis testing. The t-test results showed a t-count of 10.283 and a t-table value of 2.036, where tcount ≥ ttable. Therefore, H0 was rejected and H1 was accepted, indicating a significant effect of the PjBL-STEM model on students’ cognitive ability in junior high school.